Transperitoneal Laparoscopic Ureterolithotomy for Large Distal Ureteric Stone: The first Experience in Hasan Sadikin Hospital, Bandung - Bacilius Agung Priyosantoso; Sawkar Vijay Pramod (Jurnal llmu Bedah Indonesia, 2014)
Background. Laparoscopic ureterolithotomy has become an alternative to open surgery for removing large stones that is not amenable to endoscopic treatment. In most of the published literature, laparoscopic ap- proach for lower ureteric stone is described to be less successful than middle and upper ureter. Identifica- tion in anatomical landmarks and exposing the distal ureter has been the major boundaries in establishing laparoscopic distal ureteral stone. We hope to provide clarity and feasibility that may increase our knowledge in laparoscopic ureterolithotomy for large distal ureteral stone. Aim. The obbjective is to share our experience in laparoscopic ureterolithotomy for large distal ureteric stone with transperitoneal approach Methods. A 37 years old male has been diagnosed with a right hydronephrosis due to proximal ureterolithiasis and stone at left calyx inferior, first and stone migrated to right distal ureter on 12 hours prior surgery. He underwent laparoscopic ureterolithotomy with transperitoneal approach. Results. We successfully perform laparoscopic ureterolithotomy with transperitoneal approach on a 37 y.o male patient who diagnosed with a a right hydronephrosis due to distal ureterolithiasis and stone at left calyx inferior. Duration of operation was 45 minutes. Patient was discharged at 2nd postoperative day without any complications. Conclusion. A Transperitoneal laparoscopic ureterolithotomy for distal ureteric stone is a safe and feasible technique that should be an options on every patients who plan to undergo distal ureterolithotomy especially large stone